Design and Build a Product Sales Application at PT. Prima Fabian Mandiri Web-Based - Hartati, Eka; Yuniansyah, Yuniansyah; Airina, Ayu; Wanandi, Vernanda Septia (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The focus of this research is to create a product sales application that can help and simplify the process of selling to product delivery, and can provide information about the company and the latest stock and prices at PT. Prima Fabian Mandiri Palembang City. Design/method/approach: The system development method uses the prototype method, while the system modeling uses UML (Unified Modeling Language) in the form of use cases, activity diagrams, sequence diagrams, and class diagrams. The application also conducts testing using black box testing and after that an usability evaluation is carried out using the Use Questionnaire method with a total of 30 respondents. Questionnaires are created and distributed online using google forms. Based on the results of validity and reliability tests calculated using SPSS 25. The results of this study resulted in a product delivery application, and can provide information about the company and the latest stock and prices at PT. Prima Fabian Mandiri Palembang City. The system testing technique used in this study was black box testing, and usability evaluation was carried out using the Use Questionnaire. Based on the results of validity and reliability tests calculated using SPSS 25, all statements are declared valid and reliable so that from the five variables it shows that consumers are satisfied with the usefulness of the PT application. Prima Fabian Mandiri Palembang City. Users of this product sales application are admins, consumers, logistics and company leaders.